Narcostates: civil war, crime, and the war on drugs in Mexico and Central America - Marcy, William L. (Lynne Rienner Publishers, 2023)
Unravels the tangled web of violence, corruption, and political instability that has empowered drug trafficking organizations across Mexico and Central America since the 1970s